2016
DOI: 10.1111/cogs.12474
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity of Sound Symbolic Correspondences in Spoken Language

Abstract: Although language has long been regarded as a primarily arbitrary system, sound symbolism, or non-arbitrary correspondences between the sound of a word and its meaning, also exists in natural language. Previous research suggests that listeners are sensitive to sound-to-meaning correspondences. However, little is known about the specificity of these mappings. The present study investigated whether sound symbolic properties correspond to specific meanings, or whether these properties generalize across semantic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 104 publications
(157 reference statements)
5
19
0
Order By: Relevance
“…The pervasiveness of sound symbolism across languages supports the theory that it may have an important role in language learning (Imai et al, 2015;Kantartzis, Imai, & Kita S, 2011;Tzeng, Nygaard, & Namy, 2017). Individuals are even able to correctly assign meanings of synonym/antonym pairs above chance for languages with which they are unfamiliar (Kunihara, 1971;Nygaard et al, 2009;Tzeng, Nygaard, & Namy, 2016). Our study suggests that one potential motivated connection between sound and meaning is the set of acoustic properties to which listeners are sensitive and that translate systematically into a set of visual properties.…”
Section: Sound Symbolism In Language Acquisitionsupporting
confidence: 74%
See 1 more Smart Citation
“…The pervasiveness of sound symbolism across languages supports the theory that it may have an important role in language learning (Imai et al, 2015;Kantartzis, Imai, & Kita S, 2011;Tzeng, Nygaard, & Namy, 2017). Individuals are even able to correctly assign meanings of synonym/antonym pairs above chance for languages with which they are unfamiliar (Kunihara, 1971;Nygaard et al, 2009;Tzeng, Nygaard, & Namy, 2016). Our study suggests that one potential motivated connection between sound and meaning is the set of acoustic properties to which listeners are sensitive and that translate systematically into a set of visual properties.…”
Section: Sound Symbolism In Language Acquisitionsupporting
confidence: 74%
“…These studies show that the existence of sound-symbolic CCs in language is both prolific and robust. Further, language users are sensitive to sound-symbolic correspondences in that they actively utilize these associations to correctly assign meaning to foreign synonym-antonym pairs at above-chance levels (Nygaard, et al, 2009;Revill et al, 2014;Tzeng, Nygaard, & Namy, 2016). Soundsymbolic CCs also seem to play a role in language processing and early word learning (Imai & Kita, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that nearly all experimental demonstrations of iconicity have investigated concrete meanings [8], such as the famous kiki/bouba stimuli which are associated with spiky or round visual shapes [131,132]. To the extent that semantic generalizability of iconic forms has been experimentally demonstrated, this generalizability is of a limited type [83]. By pitting semantic notions of size (e.g.…”
Section: (A) Iconic Words Are Less Abstractmentioning
confidence: 99%
“…The results of an experiment on phonetic symbolism (D'Anselmo, Prete, Zdybek, Tommasi, & Brancucci, 2019) demonstrated that the participants were able to guess the meaning of unfamiliar spoken words due to the symbolic nature of their acoustic properties. Three experiments carried out by Tzeng, Nygaard and Namy (2016) also proved that the sound properties contributed to the inferring of word meaning. Fónagy (2001) showed that there is a certain set of associations for each phoneme at the level of articulation.…”
Section: Background and Related Researchmentioning
confidence: 81%